Health Utility and Symptom Scores in Patients With Advanced Malignant Pleural Mesothelioma Treated in a Real-World Setting - Abhenil Mittal, MD; Louis Everest, MPH; Devalben Patel, BSc, MLT; Luna J. Zhan, MPH; M. Catherine Brown, MSc; Fatemah Zaeimi, BSc; Sabine Schmid, MD; Khaleeq Khan, HBSc; Kristen Dietrich, MD; Karmugi Balaratnam, MD; Miguel Garcia Pardo de Santayana, MD; Lawson Eng, MD, FRCPC; et al. (JTO Clinical and Research Reports)
Introduction: There is a paucity of real-world associations between EQ-5D-generated health utility scores (HUS), symptoms as measured by the Edmonton Symptom Assessment System (ESAS), and the patient-reported outcomes version of the common terminology criteria for adverse events (pro-CTCAE), and survival in patients with advanced Malignant Pleural Mesothelioma (aMPM). Methods: Clinico-demographic variables and treatment information were captured retrospectively in patients diagnosed with aMPM between January 2004 and February 2021 at Princess Margaret Cancer Centre. Quality of life outcomes were measured using HUS, ESAS, and pro-CTCAE scales, by stable versus progressive disease and line-of-treatment states. Survival by mean ESAS scores were analyzed using the Kaplan-Meier method. Results: Of the 262 patients, the median age was 69 years (interquartile range: 62–74), 77% were male individuals, 52% were ever-smokers, 67% were the epithelioid-subtype, and 62% received first-line systemic therapy for advanced disease. The mean baseline HUS at diagnosis was 0.68 (95% confidence interval: 0.62–0.74) with most symptoms consisting of pain, dyspnea, and fatigue. Pooled ESAS physical and psychological scores changed significantly with disease state: the mean scores were worst at baseline, improved with stable or responding disease (physical, p < 0.001; psychological, p < 0.001), and worsened at progressive disease (physical: p < 0.001; psychological, p < 0.001). Similar trends were seen in HUS and pro-CTCAE symptom severity/frequency. Patients with high baseline ESAS physical symptom burden had inferior overall survival (median = 8.9 [high] versus 12.6 months [low], p = 0.022). Weak-to-moderate correlations were observed between most ESAS domains and HU and between pro-CTCAE domains and HU. The strongest domain correlations were with well-being, shortness of breath, tiredness, and depression domains. Conclusions: Baseline quality of life burden is high in patients with aMPM and is well captured by both EQ-5D and ESAS Individual ESAS and pro-CTCAE domains reported low/moderate correlations with HUS, reflecting the inability of one symptom to predict the entire disease state, thus paving the way for future mapping studies. The baseline physical symptom burden (ESAS) was prognostic of survival.